(untitled) (Research, Society and Development, 2022)
Child care encompasses numerous circumstances within the health process, which include several factors and circumstances to be evaluated. As a result, humanized care is highlighted both for hospitalized children and for health professionals, who need support and follow-up. Children with chronic conditions undergo numerous procedures in the health services until the moment of their discharge, therefore, this procedure has a sequence of care and assistance that must be carried out. Therefore, knowing the relevance of this theme, this study aimed to highlight the management of care that must be performed by health professionals in children with chronic diseases and conditions. For this, the research was carried out through a descriptive and exploratory study, of the integrative literature review type, carried out in the scientific databases LILACS and SCIELO, selecting scientific evidence from the last 5 years to compose the analysis of the results. By analyzing the literature, some important points were highlighted regarding the management of care that must be performed by health professionals in children with chronic diseases and conditions. In this context, the literature highlights that the preparation for hospital discharge involves a complex dynamic and suffers from several difficulties in the health services, including the difficulty of actions that are directly related to the preparation of the discharge carried out by the multidisciplinary team.